Digital Literacy: Fundamental Competence for Modern Society - Mujiono, Mujiono (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2024)
This research highlights the significance of digital literacy in our increasingly interconnected modern society through information technology. It addresses the primary challenges faced by modern society in managing information in the digital era, including the spread of fake news and data privacy breaches. The research aims to elucidate the contribution of digital literacy in addressing these challenges faced by modern society and identify its positive impacts in safeguarding data security, combating misinformation, and enabling active participation in the digital community. The research methodology employed a systematic literature review (SLR) to gather, evaluate, and synthesize literature related to modern society and digital literacy. The findings of the research reveal that digital literacy plays a pivotal role in assisting individuals in comprehending, filtering, and assessing information encountered online while safeguarding their privacy in the digital environment. In conclusion, digital literacy is not just a technical skill but also the key to responsibly and wisely harnessing digital opportunities.